Pregnancy and cardiac disease - Elliot, C; Sliwa, K; Burton, R (My University, 2014)
Medical disorders in pregnancy are one of the top five causes of maternal mortality in South Africa (SA), cardiac disease (CD) being the main contributor to this group. In developed countries, surgically corrected congenital heart disease (CHD) comprises the greater proportion of maternal deaths from CD. In SA and other developing countries, acquired heart disease such as rheumatic heart disease and cardiomyopathies are the major causes, although CHD remains significantly represented. Both congenital and acquired cardiac lesions may present for the first time during pregnancy. CD may also occur for the first time during or after pregnancy, e.g. peripartum cardiomyopathy. The risk to both the mother and the fetus increases exponentially with the complexity of the underlying disease. Generally, the ability to tolerate a pregnancy is related to: (i) the haemodynamic significance of any lesion; (ii) the functional class – New York Heart Association classes III and IV have poorer outcomes; (iii) the presence of cyanosis; and (iv) the presence of pulmonary hypertension. While the ideal time to assess these factors is before conception, women frequently present when already pregnant. This review discusses risk assessment and management of CD in pregnant women and the role of a combined cardiology and obstetric clinic.
PK
Keywords: Pregnancy; Heart diseases; Pregnancy Complications, Cardiovascular